2017
DOI: 10.1248/bpb.b17-00394
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Carrier-Mediated Transport at the Blood–Cerebrospinal Fluid Barrier in Spermine Clearance from Rat Brain

Abstract: Spermine is the end-product in the polyamine biosynthetic pathway, and its excess accumulation induces neuroexcitatory responses and neurotoxicity. The purpose of this study was to elucidate the involvement of transport systems at the brain barriers in the clearance of spermine. In vivo rat spermine elimination from brain parenchyma across the blood-brain barrier (BBB) and blood-cerebrospinal fluid (CSF) barrier (BCSFB) was assessed by intracerebral and intracerebroventricular administration techniques, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…13,14,40 Concentrations of Spd and Spm in the basal ganglia gradually decrease in normal aging. 41 Taken together, decreased serum Spm detected in PD in the current study may indicate that brain Spm decreases via the BCSFB. 41 Taken together, decreased serum Spm detected in PD in the current study may indicate that brain Spm decreases via the BCSFB.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…13,14,40 Concentrations of Spd and Spm in the basal ganglia gradually decrease in normal aging. 41 Taken together, decreased serum Spm detected in PD in the current study may indicate that brain Spm decreases via the BCSFB. 41 Taken together, decreased serum Spm detected in PD in the current study may indicate that brain Spm decreases via the BCSFB.…”
Section: Discussionsupporting
confidence: 59%
“…Concentrations of Spd and Spm in the basal ganglia gradually decrease in normal aging . Experimentally, Spm clearance from the brain parenchyma mainly occurs via the blood–CSF (BCSFB) rather than the blood–brain barrier . Taken together, decreased serum Spm detected in PD in the current study may indicate that brain Spm decreases via the BCSFB.…”
Section: Discussionmentioning
confidence: 99%
“…Inoue et al showed that patients with neurodegenerative diseases such as Alzheimer’s disease have increased spermidine levels in the frontal and parietal lobes of the brain [ 287 ]. Although polyamines cannot cross the BBB, their brain concentrations can be reflected in the blood via cerebrospinal fluid [ 288 ]. Sternberg et al showed that serum levels of spermidine in patients with mild cognitive function are higher than those of healthy controls.…”
Section: Possible Role Of Polyamine In Cognitive Functionmentioning
confidence: 99%
“…Such a steep gradient of PA concentrations between blood plasma and CSF, extracellular brain space, cytoplasm, and total PA content in cells requires explanation. Most likely, the systems use different transporters [62].…”
Section: Concentrations and Transport Of Polyamines Within The Brainmentioning
confidence: 99%